Lexical Density and Frequency of the Lexical Words in A Children’s Storybook: Alice In Wonderland (Simplified Version Published in 2024 by Mind to Mind) - Annisa Zulfarani Salsabila; Arafiq Arafiq; Mh. Isnaini; Kamaludin Yusra (Program Studi Pendidikan Bahasa Inggris, 2026)
This study analyzes the lexical density, word frequency, readability, and suitability of Alice in Wonderland (Simplified Version published in 2024 by Mind To Mind) for young learners of English as a Foreign Language (EFL). Using a mixed-method approach, the text was examined to see how many content words it contains, how often key vocabulary appears, how easy it is to read, and how the text supports understanding through illustrations. The results show that the book has an average lexical density of 52%, meaning it provides enough vocabulary input while still being easy to understand. Frequent repetition of important words helps children learn vocabulary naturally. Readability testing also shows that the book is suitable for elementary-level learners. Around 60–65% of the words are supported by pictures, helping children understand the story more easily. Overall, the simplified book is appropriate for young EFL learners and can support vocabulary development and reading comprehension. However, the study only examined one book and did not involve real students, so further research with more storybooks and classroom testing is suggested.